Lactobacillus rhamnosus GG as an Effective Probiotic for Murine Giardiasis - Nisha Goyal; Ram Prakash Tiwari; Geeta Shukla (Interdisciplinary Perspectives on Infectious Diseases)
The gut microflora is an important constituent in the intestinal mucosal barrier and has been introduced as the concept of probiotic therapy that beneficially affects the host by improving its intestinal microbial balance. Therefore, the main objective of the study was to explore the protective potential of various lactobacilli strains for murine giardiasis. By experimentation, it was found that the probiotic supplementation of either Lactobacillus casei, L. acidophilus, L. plantarum, or L. rhamnosus GG, 7 days prior to inoculation with G. lamblia trophozoites, reduced the rate of cyst excretion compared with Giardia-infected mice. Interestingly, L. GG was found to be the most effective probiotic in reducing the duration of giardia cycle and acts as an effective prophylactic probiotic for murine giardiasis but needs to be clinically correlated due to entirely different human microflora.